Validation and psychometric properties of Bahasa Malaysia version of the depression anxiety and stress scales (DASS) among diabetic patients - Musa, Ramli; Mohd Ali, Salmiah; Musa, Nurul Ain (Malaysian Psychiatric Association, 2009)
Background: Having a validated questionnaire in any field would nurture a research path in that particular area. The aim of this study was to validate the Depression Anxiety Stress Scales 21-item (DASS-21) Bahasa Malaysia BM) version among clinical subjects who were diabetic patients. Objectives: To determine the reliability and construct validity of the BM DASS by looking at internal consistency and exploratory factor analysis respectively. Methods: The BM DASS was administered to a total of 153 diabetic patients. These patients were selected when they came to 15 retail pharmacies all over the Klang Valley. Results: The BM DASS-21 had very good Cronbach’s alpha values of 0.75, 0.74 and 0.79, respectively for depression, anxiety and stress subscales. For construct validity, it also had good factor loading values for 17 out of 21 items (.31 to .75). Conclusions: The results of this study entrenched the evidence that the BM DASS-21 had excellent psychometric properties and therefore it is suitable to be used for the Malaysian clinical population.